Polemik Penamaan Restoran â€œBabiamboâ€ dan Hubungannya dengan Filosofi Minangkabau â€œAdaik Basandi Syarak, Syarak Basandi Kitabullahâ€: Sebuah Studi Linguistik Forensik: Sebuah Studi Linguistik Forensik - Intan Kusuma Wulandari (Madah: Jurnal Bahasa dan Sastra, 2024)
Urang Awak 'Orang Minang' is an ethnicity in West Sumatra Province, Indonesia, and is also widely known for its traditional food in Padang Restaurant. The naming of the Babiambo restaurant in Jakarta which is identified as a typical Minang Babiambo restaurant, babi 'babi' and ambo 'saya' (my pig) is allegedly considered an insult to the identity of the Minang people. This study discusses the naming of the restaurant "Babiambo" and its relation to the philosophy of "Adaik basandi Syarak, Syarak basandi Kitabullah" as a guideline for Minang society based on forensic linguistic glasses with cognitive linguistic analysis and semiotics. Qualitative research methods with a descriptive approach were used in this study. Data collection techniques are carried out by observation methods and literature studies. The results of this study found that the naming of the padang restaurant "Babiambo" from cognitive and semiotic analysis showed that there was no insult to Minang identity in the process of its formation.